Uruguay : Income Transfer Policies in Uruguay, Closing the Gaps to Increase Welfare - World Bank (Washington, DC, 2012)
Uruguay's Government is currently analyzing several reform strategies for the social sectors. These include a health reform, the introduction of a new poverty alleviation program, possible changes in pensions and unemployment insurance, and also a tax reform, that impacts the income transfer policies in several aspects. The purpose of this report is to contribute to the debate around the design of the income transfer policies for the medium and long term. The report is divided in five sections. Section two presents the conceptual discussion; section three describes the current policies, including an assessment of coverage, impacts, and fiscal effects. The fourth section presents a simulation to assess the potential impacts of the new Plan de Equidad, and the fifth section discusses conclusions and the central challenges for the future.